Market Dominance and Law Enforcement under Indonesian Competition Law: An Analysis of Law No. 5 of 1999 - Abdul Kamid; Dadi Susilo; Kristanto Kristanto; Lukman Matnudin; Anto Kustanto (APPTHI, 2025)
Indonesian competition law plays a vital role in preventing monopolistic practices and ensuring fair competition. Yet, the rise of the digital economy, shifting market structures, and persistent enforcement challenges have complicated regulation of market dominance. This study analyzes the main provisions of Law Number 5 of 1999, examines the concept of market dominance, and evaluates enforcement mechanisms. Using a normative legal research method with statute, conceptual, and doctrinal approaches, data were collected from legislation, KPPU regulations, and academic literature. Findings show that Indonesian competition law applies a rule of reason, targeting abuse of dominant positions rather than dominance itself. Market dominance is assessed through indicators such as market share, control of essential facilities, barriers to entry, exclusionary conduct, and independence from competitive pressures. KPPU plays a central role despite institutional and evidentiary limitations. This research contributes to competition law scholarship and offers concise policy recommendations to strengthen enforcement in the digital era.